Quarter tone techniques used on western flute in 'Orange Dawn' by Ian Clarke / Arif Ismail Shamsuri. - Shamsuri, Arif Ismail (2020)
Quarter-tone is a type of pitch that exist in musical sound. It can be defined as the tone that was generated between the half-tones. This type of tone, which is quarter-tone, often can be heard in Middle-East music especially in Arabic music. In Arabic music, the scale of a piece was also different and have own named such as, Hijaz Scale, Maqam Scale and other. In Western music, quarter-tones were rarely used in a piece. Quartertone just can be found in modern music. However, a composer named Ian Clarke, managed to implicate quarter-tone in flute playing. There were several of his works that have quarter-tone techniques include in his composition. For this study, the author had select one of Clarke's composition entitled, 'Orange Dawn'. This piece contains the note that need to be played as quarter-tone. The main purpose of this study is to investigate the quarter-tone techniques used on Western flute playing in 'Orange Dawn' piece, and to find out the approach to practice the quarter-tones techniques on the Western flute playing in 'Orange Dawn' piece, composed by Ian Clarke. Several interviews have been done by the author in order to get the finding of the study. The interview was conducted among two flutes lecturers, and four flutes students, in the Faculty of Music, UiTM Shah Alam. The author uses semi-structured method of questionnaire to interview the participants. There were six to seven questionnaire had been asked to every participant. The author also analyse the 'Orange Dawn' score in order to investigate the quarter-tone in the piece. The preliminary result shows that the composer uses the quarter-tone in the piece because he wants to create an atmosphere and tried to implicate the environment of the dawn for the listener. The author also found that the fingering chart have been provided in the score by the composer for the flutist to be able to play the quarter-tone notes. Following some in-depth analysis, some recommendations for the study are presented.